Analisis Campur Kode dan Alih Kode pada Akun Instagram “OVERHEARDJKT” - Sirikanda Sakulpimolrat; M.R. Nababan (Universitas Sebelas Maret, 2026)
This is a descriptive qualitative study that aims to describe the forms and causes of code-mixing and code-switching in posts from the Instagram account